DIR/floortime Approach to Improve Two-way Communication Skills in Children with Autism Spectrum Disorder - Hana Lazuardy Rahmani; Lia Mawarsari Boediman (Psikostudia : Jurnal Psikologi, 2024)
The limited ability to engage in two-way social communication poses a significant challenge for children with Autism Spectrum Disorder (ASD). Nevertheless, proficiency in two-way social communication is a crucial skill that children need to foster for their overall development. This study employs a single-subject design (n=1), focusing on early childhood and involving fathers as the primary caregivers. The primary objective is to assess the effectiveness of the DIR/Floortime approach, specifically in enhancing communication skills in children with autism spectrum disorders. This study consisted of 16 sessions which divided into pre-intervention, intervention, and post-intervention sessions. Measurement was conducted using the Circle of Communication (CoC) observation sheet and the Functional-Emotional Assessment Scale (FEAS) to compare participant change in score trends between pre-intervention and post-intervention phases. The research findings indicate that the application of DIR/Floortime principles effective in improving the two-way communication abilities of children with autism spectrum disorders. Consequently, this approach can be considered as an alternative consideration for the intervention of children with autism spectrum disorders.Minimnya kemampuan untuk melakukan komunikasi sosial dua arah menjadi salah satu masalah utama pada anak dengan Autism Spectrum Disorder (ASD) atau Gangguan Spektrum Autisme. Padahal, kemampuan komunikasi sosial dua arah merupakan salah satu kemampuan penting yang perlu dimiliki oleh anak agar dapat menunjang perkembangannya. Penelitian ini merupakan penelitian single subject design (n = 1) pada anak usia dini dan ayah sebagai pengasuh utama anak yang bertujuan untuk mengetahui efektivitas dari pendekatan DIR/Floortime khususnya dalam meningkatkan kemampuan komunikasi pada anak dengan gangguan spektrum autisme. Penelitian terdiri dari 16 sesi yang terbagi menjadi sesi pra-intervensi, intervensi, dan sesi post-intervensi. Pengukuran menggunakan lembar observasi Circle of Communication (CoC) dan Functional-Emotional Assessment Scale (FEAS) untuk membandingkan perubahan tren skor partisipan pada pra-intervensi dan post-intervensi. Hasil penelitian menunjukkan bahwa penerapan prinsip-prinsip DIR/floortime dapat meningkatkan kemampuan komunikasi dua arah anak dengan gangguan spektrum autisme. Oleh karena itu, pendekatan ini dapat dijadikan salah satu pertimbangan alternatif penanganan anak dengan gangguan spektrum autisme.